PEMBELAJARAN DIGITAL STORYTELLING DALAM KONTEN MEDIA SOSIAL UNTUK GENERASI MUDA - Lydia Irena; Eldiani Febyola; Michelle Augustine; Alexandra Carolina (Jurnal Bakti Masyarakat Indonesia, 2025)
Indonesian teenagers currently dominate internet and social media users, with penetration rates nearly equal: 97.17% in the 19–34 age group and 99.16% in the 13–18 age group. The most frequently accessed apps include Tiktok, YouTube, Whatsapp, Instagram, and Facebook, with Tiktok leading the way in terms of monthly usage duration. Social media now serves not only as a means of communication but also as a Platform for self-expression, entertainment, and a space for creating economic opportunities. The development of social media has made the younger generation both users and producers of digital content. However, many of them do not yet understand the importance of storytelling in creating inspiring, educational, and character-building content. As a result, the content produced is often instantaneous, shallow, and even has the potential to have negative impacts. Various studies confirm that the application of digital storytelling can improve message quality, deepen communication meaning, build a positive image of the younger generation, and strengthen digital literacy. Through the integration of text, audio, visuals, and video, digital storytelling has been shown to foster learning motivation, collaboration skills, and critical and creative thinking skills. Furthermore, authentic narratives that are close to the audience's experiences strengthen trust, create emotional bonds, and help teenagers explore their identity. At the same time, SMA Santa Maria 1 Cirebon's partner also experienced limited technical skills in content production with digital storytelling and expert guidance. Therefore, the solution offered is a Student Creativity Program (PKM) titled "Digital Storytelling Learning in Social Media Content for the Younger Generation," which aligns with Tarumanagara University's PKM roadmap, namely "Building Public Awareness Towards an Information Society." The PKM was conducted through seminars and Workshops on social media content creation, emphasizing the concept of digital storytelling. The results of the activity indicate that senior high school students were able to understand the fundamental concepts of digital storytelling effectively when the learning process was delivered in an interactive and application-oriented manner. Students recognized that storytelling enhances the appeal of content. This activity also contributed to the improvement of students’ media literacy and their readiness to engage with the digitally driven creative economy.   ABSTRAK Remaja Indonesia saat ini menempati posisi sebagai pengguna internet dan media sosial paling dominan, dengan tingkat penetrasi hampir merata, yakni 97,17% pada kelompok usia 19–34 tahun dan 99,16% pada kelompok usia 13–18 tahun. Aplikasi yang paling banyak diakses meliputi Tiktok, YouTube, Whatsapp, Instagram, dan Facebook, dengan Tiktok menempati urutan pertama dari sisi durasi penggunaan bulanan. Media sosial kini berfungsi tidak hanya sebagai sarana komunikasi, melainkan juga wadah ekspresi diri, hiburan, sekaligus ruang penciptaan peluang ekonomi. Perkembangan media sosial telah menjadikan generasi muda sebagai pengguna sekaligus produsen konten digital. Namun, banyak di antara mereka yang belum memahami pentingnya narasi (storytelling) dalam membangun konten yang inspiratif, edukatif, dan berkarakter. Akibatnya, konten yang diproduksi sering bersifat instan, dangkal, bahkan berpotensi menimbulkan dampak negatif. Berbagai studi menegaskan bahwa penerapan digital storytelling mampu meningkatkan kualitas pesan, memperdalam makna komunikasi, membangun citra positif generasi muda, serta memperkuat literasi digital. Melalui integrasi teks, audio, visual, dan video, digital storytelling terbukti menumbuhkan motivasi belajar, kemampuan kolaborasi, serta keterampilan berpikir kritis dan kreatif. Lebih jauh, narasi yang autentik dan dekat dengan pengalaman audiens memperkuat kepercayaan, menciptakan ikatan emosional, sekaligus membantu remaja mengeksplorasi identitas diri. Bersamaan dengan itu, mitra SMA Santa Maria 1 Cirebon juga mengalami keterbatasan keterampilan teknis produksi konten dengan digital storytelling dan pendampingan ahli. Sehingga solusi yang ditawarkan adalah PKM bertajuk “Pembelajaran Digital Storytelling dalam Konten Media Sosial untuk Generasi Muda,” yang sejalan dengan dengan roadmap PKM Universitas Tarumanagara, yaitu "Membangun Kesadaran Publik Menuju Masyarakat Informasi". PKM dilakukan dengan metode seminar dan Workshop pembuatan konten media sosial dengan mengedepankan konsep digital storytelling. Hasil kegiatan menunjukkan bahwa siswa SMA mampu memahami konsep dasar digital storytelling dengan baik ketika pembelajaran dikemas secara interaktif dan aplikatif. Siswa memahami bahwa storytelling memperkuat daya tarik konten. Kegiatan ini juga berkontribusi pada peningkatan literasi media dan kesiapan siswa menghadapi era ekonomi kreatif berbasis digital.